Empirical comparison of three assessment instruments of clinical reasoning capability in 230 medical students - Yvonne Covin; Palma Longo; Neda Wick; Katherine Gavinski; James Wagner (BMC Medical Education, 2020)
Abstract Background Several instruments intend to measure clinical reasoning capability, yet we lack evidence contextualizing their scores. The authors compared three clinical reasoning instruments [Clinical Reasoning Task (CRT), Patient Note Scoring rubric (PNS), and Summary Statement Assessment Rubric (SSAR)] using Messick’s convergent validity framework in pre-clinical medical students. Scores were compared to a validated clinical reasoning instrument, Clinical Data Interpretation (CDI). Method Authors administered CDI and the first clinical case to 235 students. Sixteen randomly selected students (four from each CDI quartile) wrote a note on a second clinical case. Each note was scored with CRT, PNS, and SSAR. Final scores were compared to CDI. Results CDI scores did not significantly correlate with any other instrument. A large, significant correlation between PNS and CRT was seen (r = 0.71; p = 0.002). Conclusions None of the tested instruments outperformed the others when using CDI as a standard measure of clinical reasoning. Differing strengths of association between clinical reasoning instruments suggest they each measure different components of the clinical reasoning construct. The large correlation between CRT and PNS scoring suggests areas of novice clinical reasoning capability, which may not be yet captured in CDI or SSAR, which are weighted toward knowledge synthesis and hypothesis testing.